Calibration and orientation of cameras in computer vision (Koros Press Limited, 2015)
This book brings together concepts and approaches from the fields of photogrammetry and computer vision. In particular, it examines techniques relating to quantitative image analysis, such as orientation, camera modelling, system calibration, self-calibration and error handling. The chapters have been contributed by experts in the relevant fields, and there are examples from automated inspection systems and other real-world cases. The book provides study material for students, researchers, developers and practitioners